Graph-theoretic concepts in computer science : 41st International Workshop, WG 2015 Garching, Germany, June 17-19, 2015, revised papers /: 41st International Workshop, WG 2015 Garching, Germany, June 17-19, 2015, revised papers. (2016) - Unknown
No abstract available